1994
DOI: 10.2514/3.46490
|View full text |Cite
|
Sign up to set email alerts
|

Experimental studies of vortex flaps and vortex plates

Abstract: Low-speed wind-tunnel tests have been made on a number of vortex flap and vortex plate configurations at the Cranfield Institute of Technology. The objectives of the experiment are to assess the benefits of these devices on the lift/drag ratio improvement of delta wings. The force and surface pressure measurements were made on a 1.15-m span, 60-deg delta wing model. Results indicate that the vortex flap deflection angle, which causes the flow to attach on the flap surface without any large separation, shows a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 2 publications
1
8
0
Order By: Relevance
“…This effect does however result in improved high a performanceas the maximum lift coef cient peak occurs at higher a . 6 Performance of a wing with vortex aps improves overall, as the reduction in drag outweighs the loss of lift. LEVF performance is limited by the inboard migration and expansion of the leading-edge vortices with incidence.…”
Section: Nomenclaturementioning
confidence: 98%
“…This effect does however result in improved high a performanceas the maximum lift coef cient peak occurs at higher a . 6 Performance of a wing with vortex aps improves overall, as the reduction in drag outweighs the loss of lift. LEVF performance is limited by the inboard migration and expansion of the leading-edge vortices with incidence.…”
Section: Nomenclaturementioning
confidence: 98%
“…Lower-surface leading-edge plates have been evaluated by Traub [13], Rinoie and Stollery [14], and Rao and Johnson [15] as a means of enhancing the performance of delta wings and delta wings with vortex flaps by augmenting and concentrating leading-edge vortex suction. The plate was constituted of a thin metal sheet attached below the leading edge and projecting out so as to be coincident with the leading edge when viewed from above.…”
Section: Introductionmentioning
confidence: 99%
“…Many tests have been made which confirm the benefit of the LEVF (Campbell and Osborn, 1986). The author has made experimental studies using delta wing models that have sweepback angles L of 50°, 60°and 70°, fitted with tapered vortex flaps (Rinoie and Stollery, 1994;Rinoie et al, 1997;Rinoie, 1997). Purposes of these studies were to confirm the benefit of the LEVF and to know how the difference of the sweepback angle affects the aerodynamic characteristics of the wing with the LEVF.…”
Section: Introductionmentioning
confidence: 99%
“…Throughout these studies, it was revealed that the highest lift/drag ratio for the 60°delta wing is achieved using a modest LEVF deflection angle that causes the flow to attach on the flap surface without any large separation (Rinoie and Stollery, 1994). On the contrary, the maximum lift/drag ratio for the 70°delta wing is attained, when a separated region is formed on the vortex flap and when the spanwise length of this separated region almost coincides with the vortex flap width .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation